PECULIARITIES OF STIMULATION OF OVULATION IN WOMEN WITH POLYCYSTIC OVARIAN SYNDROME OF DIERENT AGE - M. P. Mironova; E. A. Fazlieva (Акушерство, гинекология и репродукция, 2016)
The aim of this work was to estimate the effectiveness of stimulation of ovulation in women with polycystic ovarian syndrome (PCOS) in different age groups depending on existence of previous pregnancies.Methods: The design was retrospective, observational, unicentral study. Investigation includes 62 women from 21 till 40 years old with PCOS and previous ineffective medicinal treatment. Ovarian stimulation with the use of antiestrogens (clomiphene citrate) and recombinant folliclestimulating hormone (follitropin) was conducted.The final pointwas visualization of the ovum by ultrasound investigation on the day 21 after ovulation. As the result of ovarian stimulation ovulation occurred in every case. In the group of patients before 30 years old pregnancy rate was 41,94%, in the group 30-35 years old – 38,1%, in the group older than 35 years – 20%. In the groups 30-35 years old and older than 35 years old the int errelation between the effectiveness of stimulation of ovulation and existence of previous pregnancies was observed. Thus, in women with pregnancies in anamnesis the final points were achieved in 75 % (group 30-35 years old) and 25% (group older than 35 years). Without previous pregnancies stimulation of ovulation was not effective (0%) in the group of patients older than 35 years old and less effective (23,08%) in the group of patients30-35 years old. In the women younger than 30 years the correlation between effectiveness of stimulation ofovulation and existence of previous pregnancies was not observed.Conclusion: In the group of patients older than 30 years old stimulation of ovulation have higher effectiveness amongwomen with pregnancies in anamnesis.